Characterization of mineral contents on androgen deficient and chronic ethanol consuming rats by biochemistry and non-destructive techniques - Lodi, K. Bortolin [UNESP]; da Silva, J. R.; Carvalho, C. da Silva; da Rocha, R. F.; do Espirito Santo, A. M. (Medimond S R L, 2009)
Ethanol can compromise the body mineral composition and affect bone, and when associated to hypogonadism is considered an important risk factor for osteoporosis in man. The aim of this study was to investigate the effect of androgen deficient and chronic ethanol consuming on mineral contents by biochemistry and non-destructive techniques. Wistar rat (n=54) were divided in orchiectomy (ORQ) or SHAM-operated and subdivided by diet. They were daily fed with a Lieber DeCarli diet model for 8 weeks long. The controls groups were free-diet and pair-fed. Ca and P were analyzed by biochemistry test in the blood and by nX-ray fluorescence and FT-Raman on the femur area. Serum analysis revealed hypocalcaemia and hypeiphosphataemia in ethanol groups more than pair-fed and free-diet. In similarity, spectroscopy indicated a decrease in bone Ca content in ORQ groups, mainly for ethanol groups. Phosphorus content and Ca/P molar ratio, otherwise, doesn't diverge in all 6 groups. Ethanol consumption impaired Ca and P homeostasis in ORQ rat more than SHAM. The relationships among ethanol consume and androgen deficit support the hypothesis that ethanol affects the mineral-regulating hormones and may mediate some effects on bone. These findings demonstrate that ethanol seemed to interfere with the normal compensatory response to these Ca and P levels and is more significant M androgen deficiency rats.